Anti-Inflammatory Activity Test of Tapak Liman (Elephantopus scaber L.) Leaf Extract Using Red Blood Cell Membrane Stabilization Method - Wahdaniah, Wahdaniah; Yanti, Rahmi; Kamilla, Laila; Salim, Maulidiyah (Jurnal Laboratorium Khatulistiwa, 2025)
Inflammation is the reaction of living tissue to trauma or infection, both in acute and chronic conditions. One plant with anti-inflammatory potential is the tapak liman leaf (Elephantopus scamber L.), which contains secondary metabolites such as phenolics, flavonoids, tannins, alkaloids, steroids/treponoids, and saponins. The purpose of this study was to determine the anti-inflammatory activity of Elephantopus scamber L. leaf extract at concentrations of 0.005%, 0.01%, 0.02%, 0.04%, and 0.08% using the red blood cell membrane stability method. Anti-inflammatory activity showed that 70% ethanol extract of tapak liman leaves had low anti-inflammatory activity at a concentration of 0.005% with a stability of 98.00%, while the highest activity was found at a concentration of 0.08% with a stability of 99.65%. Microscopic examination showed that at concentrations of 0.005%, 0.01%, 0.02%, 0.04%, and 0.08%, the administration of tapak liman extract could restore the normal shape of erythrocytes. The Kruskal-Wallis test yielded a significance value of 0.000, which is less than 0.05, meaning that Ha is accepted. It can be concluded that there are differences in the anti-inflammatory activity of tapak liman leaf extract (Elephantopus scamber L.) at concentrations of 0.005%, 0.01%, 0.02%, 0.04%, and 0.08%.